The Importance and Efficiency of Organizing Reversible Traffic Flow in the Conditions of Uzbekistan - Shermatov Shamshir (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article provides a scientific analysis of the relevance, efficiency, and practical significance of organizing reversible road traffic in the cities of Uzbekistan, particularly in Tashkent. The main principles of the reversible system for managing transport flows, the conditions for its implementation, and its economic and environmental impact are considered. The experience of foreign countries and the possibilities of adaptation to the conditions of Uzbekistan will be analyzed.